2012
DOI: 10.1093/geront/gns052
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Neighborhood Social Cohesion and Social Capital for the Well Being of Older Adults in the Community

Abstract: The results of this study support the importance of social capital of individuals, as well as social capital within the neighborhood and social cohesion within the neighborhood for well being of older adults. The well being of older adults may also be enhanced through the improvement of quality of neighborhood services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
273
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(315 citation statements)
references
References 43 publications
16
273
2
4
Order By: Relevance
“…Our study also found that perceived social cohesion and social interaction were positively associated with SWB, which was consistent with our hypotheses and previous studies (16,18,51,52). Social cohesion and social interaction may influence elders' SWB in several ways.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also found that perceived social cohesion and social interaction were positively associated with SWB, which was consistent with our hypotheses and previous studies (16,18,51,52). Social cohesion and social interaction may influence elders' SWB in several ways.…”
Section: Discussionsupporting
confidence: 93%
“…These associations with mental health could be expected to extend to SWB. This has been supported by cross-sectional studies, which have found that perceived neighborhood cohesion was positively associated with SWB among elders (8,15,16), and a longitudinal study in England (17), which found that negative neighborhood perceptions were associated with poorer SWB. Another longitudinal study in the Netherlands (18) found that social cohesion and social belonging were positively associated with SWB.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This instrument has been used extensively to investigate older people's wellbeing (e.g. Cramm et al 2013;Slotman et al 2015;Cramm and Nieboer 2015). Aging in place was assessed using statements developed in a previous study utilizing the 2007 World Health Organization (WHO) framework for age-friendly cities and additional aging in place literature (e.g., Lui et al 2009;van Dijk et al 2014; ''Appendix 2'').…”
Section: Methodsmentioning
confidence: 99%
“…[53,94,143] Further, duration of residence tends to be correlated with age, which may also be a confounder in associations between neighbourhood cohesion and health. [94,144,145] As mentioned in the preceding paragraph, personal characteristics like age, gender, marital status and socioeconomic position could affect the level of social cohesion in a given neighbourhood. Conversely, neighbourhood cohesion could influence who lives in a particular neighbourhood, as well as the length of time people reside there.…”
Section: Covariate Identification and Inclusionmentioning
confidence: 99%